Activation of Peroxisome Proliferator–Activated Receptor-δ as Novel Therapeutic Strategy to Prevent In-Stent Restenosis and Stent Thrombosis. Issue 8 (August 2016) - Hytönen, Jarkko; Leppänen, Olli; Braesen, Jan Hinrich; Schunck, Wolf-Hagen; Mueller, Dominik; Jung, Friedrich; Mrowietz, Christoph; Jastroch, Martin; von Bergwelt-Baildon, Michael; Kappert, Kai; Heuser, Arnd; Drenckhahn, Jörg-Detlef; et al.
Abstract : Objective—: Drug-eluting coronary stents reduce restenosis rate and late lumen loss compared with bare-metal stents; however, drug-eluting coronary stents may delay vascular healing and increase late stent thrombosis. The peroxisome proliferator–activated receptor-delta (PPARδ) exhibits actions that could favorably influence outcomes after drug-eluting coronary stents placement. Approach and Results—: Here, we report that PPARδ ligand–coated stents strongly reduce the development of neointima and luminal narrowing in a rabbit model of experimental atherosclerosis. Inhibition of inflammatory gene expression and vascular smooth muscle cell (VSMC) proliferation and migration, prevention of thrombocyte activation and aggregation, and proproliferative effects on endothelial cells were identified as key mechanisms for the prevention of restenosis. Using normal and PPARδ-depleted VSMCs, we show that the observed effects of PPARδ ligand GW0742 on VSMCs and thrombocytes are PPARδ receptor dependent. PPARδ ligand treatment induces expression of pyruvate dehydrogenase kinase isozyme 4 and downregulates the glucose transporter 1 in VSMCs, thus impairing the ability of VSMCs to provide the increased energy demands required for growth factor–stimulated proliferation and migration. Conclusions—: In contrast to commonly used drugs for stent coating, PPARδ ligands not only inhibit inflammatory response and proliferation of VSMCs but also prevent thrombocyte activation and support vessel re-endothelialization. Thus, pharmacological PPARδ activation could be a promising novel strategy to improve drug-eluting coronary stents outcomes. Abstract : Supplemental Digital Content is available in the text.